Quantifying the Impact of Siderite Composition and Reservoir Resistivity (Rt) on Water Saturation Estimation in Low-Resistivity Sideritic Sandstone Reservoirs Using the Graphic Plot Method - Sarju Winardi; Sugeng Sapto Surjono; Donatus Hendra Amijaya; Wiwit Suryanto (Testing Center for Oil and Gas LEMIGAS, 2024)
The case studies on low-resistivity-low-contrast (LRLC) reservoirs have started using a conductive matrix model approach based on the assumption that the rock matrix is composed of conductive minerals. The previous studies on reservoir resistivity (Rt) against conductive-minerals-rich sandstone were limited to pyritic types without developing the others such as the sideritic which was found in Indonesia. Therefore, there is a need to determine the relationship between siderite volume within the sandstone reservoir and the reduction number of Rt. Relation profiles were applied to accurately estimate the actual water saturation (Sw) while the resistance of the sandstone samples was determined through the voltage (V, volt) and current (I, ampere). The samples were designed as pseudo-core in the laboratory and simulated to have siderite composition in the range of 0-30% followed by the injection of brine at different saturation conditions. The Rt was calculated through the modification of Wenner and Ohm’s Law and later compared graphically with siderite volume of each Sw line. It was observed from the results that siderite led to an exponential reduction in Rt value. Moreover, the threshold volume of siderite required to reduce Rt significantly to 50% of the original value was found to be 6%. The actual Sw was later estimated simply through the application of the Graphic Plot Method from the curves